Investigating the Utilization of TikTok Application to Improve Nursing Students’ English Speaking Skills - Dyah Supraba Lastari; Aidil Syah Putra; Abdul Rohim (Universitas Muhammadiyah Tangerang, 2024)
In this era of the 5.0 industrial revolution, the importance of communication skills in English is becoming more pronounced, including in the field of nursing. Speaking is one of the four core skills for effective communication in the English language. The purpose of this paper is to describe nursing students’ experiences of using TikTok Application, a short-video sharing platform, as an alternative tool to help them practicing their speaking skills. The subjects of this study were 31 second-semester students of Nursing Study Program at a private University in Tangerang. The method used in this research was quasi-experimental approach with one group pretest-posttest design. The findings revealed that using the TikTok application can help students to improve their speaking skills significantly. In addition, they also gave positive responses toward using TikTok in learning English language as it could make them more relaxed and enjoyed while practicing their speaking skills.